Sarcopenia in Cancer Patients - Andree Kurniawan (Indonesian Journal of Cancer, 2019)
Introduction: Sarcopenia in cancer patients, especially in advanced stage, recently known as an emerging problem. Firstly, sarcopenia is found in elderly patients. The diagnosis of sarcopenia needs evaluation of muscle composition and function and physical activity. Sarcopenia will give negative impacts such as increased mortality, chemo-toxicity, and decreased quality of life. Here, we review the current evidence describing the definition, impact, risk factors, mechanisms, diagnosis and treatment of sarcopenia in cancer patients.Method: We identified 48 studies and/or review articles evaluating sarcopenia in cancer patients by searching PubMed and EMBASE databases. Results: Sarcopenia is reported across all stages and types of cancers. There is a new definition of sarcopenia that is reported in 2019 paper. The risk factors or causes of sarcopenia in cancer are complex depending on the clinical settings of each patient. SARC-F questionnaire can be used to screen cancer patients in clinical settings. The diagnostic evaluation and cut-off measurement of sarcopenia especially in cancer varied across studies. The loss of muscle mass that happens during chemotherapy will make a poor prognosis. Sarcopenia can worsen chemotherapy toxicity. Combination exercise with adequate dietary supplementation, adequate energy, and protein are important in the management of sarcopenia in cancer patients.Conclusions: Patients with cancer belong to a population at risk of developing sarcopenia before and after chemotherapy. Sarcopenia diagnosis needs the evaluation of muscle mass and muscle strength or physical performance. Physical activity exercise is the best strategy to reduce sarcopenia in cancer patients.